An edition of De causis torchi Corc' Oche and Aided Echach maic Maireda - De Vries, Ranke (Trinity College (Dublin, Ireland). Department of Irish and Celtic Studies, 2007)
This thesis consists of a full edition of two early Irish texts relating to the outburst of Loch nEchach ('Echu's Lake', present Lough Neagh). The titles of these tracts are De causis torchi Core’ Oche ‘On the reasons for the migration of the Corco Óche’ (Part I) and Aided Echach maic Maireda ‘The death of Echu mac Maireda’ (Part II). Part I: De causis torchi Core’ Oche (De causis) -- The text contained in Part I is very early. It consists of two prose sections and the poem Ba mol Mídend midlaige, ‘There was a prophecy of Mídenn the fool’ attributed to Luccreth moccu Chíara. This poem, which seems to be missing a few couplets and does not have a dúnad, can be dated to the seventh century, and is composed in an early form of deibide metre: the final words of each couplet in the quatrain rhyme (and generally, this rhyme is between a stressed and an unstressed syllable), but verse-lines are not yet heptasyllabic. The prose sections also contain a number of archaic forms, and can be placed slightly later, perhaps at the beginning of the eighth century. The most complete version of De causis is found in the manuscript Laud Misc. 610 (Laud), with variant versions of approximately the first half of the text in the Book of Ballymote (BE) and the Book of Lecan (Lee). It is noteworthy that while Laud is the latest of these three manuscripts, it contains the most archaic version.
Keywords: Irish, Ph.D.; Ph.D. Trinity College Dublin